2001
DOI: 10.1161/01.atv.21.4.560
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Regulates Vascular Endothelial Growth Factor Expression in Human Macrophages and Endothelial Cells Through Activation of Peroxisome Proliferator–Activated Receptor-γ

Abstract: Abstract-Vascular endothelial growth factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
87
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 46 publications
11
87
1
1
Order By: Relevance
“…34 However, although PPAR-␥ agonists have been shown previously to restore proangiogenic factors, upregulate HO-1, 10 and increase the production of VEGF in vitro [35][36][37] and in vivo, 18 rosiglitazone failed to alter angiogenic factors in the RUPP rat in the present study. A recent study, involving the induction of HO-1 in RUPP rats via the administration of cobalt (III) protoporphyrin IX chloride, demonstrated that, as a result of cobalt (III) protoporphyrin IX chloride treatment, placental expression of HO-1 was increased, and there was a significant shift in the angiostatic balance ratio (sFlt-1:VEGF).…”
Section: Discussioncontrasting
confidence: 71%
“…34 However, although PPAR-␥ agonists have been shown previously to restore proangiogenic factors, upregulate HO-1, 10 and increase the production of VEGF in vitro [35][36][37] and in vivo, 18 rosiglitazone failed to alter angiogenic factors in the RUPP rat in the present study. A recent study, involving the induction of HO-1 in RUPP rats via the administration of cobalt (III) protoporphyrin IX chloride, demonstrated that, as a result of cobalt (III) protoporphyrin IX chloride treatment, placental expression of HO-1 was increased, and there was a significant shift in the angiostatic balance ratio (sFlt-1:VEGF).…”
Section: Discussioncontrasting
confidence: 71%
“…Contradictory effects of 15d-PGJ 2 and other PPAR␥ agonists on COX-2 and VEGF expression have been described in the literature. Whereas some authors report that these agents suppress COX-2 or VEGF expression in a variety of cell lines after cell stimulation (16,17,41,42), other results indicate that 15d-PGJ 2 and other PPAR␥ agonists are inductors of COX-2 or VEGF expression (41,(43)(44)(45). Although these apparent discrepancies may have multiple causes, it is likely that 15d-PGJ 2 displays a dual effect; whereas this cyclopentenone induces basal COX-2 or VEGF expression, in most cases, presumably by PPAR␥ activation, it also is able to reduce the up-regulation of these genes by PPAR␥-dependent or -independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Increased VEGF levels have been reported in plasma from hypercholesterolemic individuals [13] and in coronary arteries from hypercholesterolemic pigs [14]. Moreover, it has been shown that oxidized LDL, a key molecule in the atherosclerotic process, can upregulate VEGF expression in macrophages and endothelial cells, at least partially through the activation of PPAR␥ [15]. In this context, assuming that VEGF acting through VEGFR-2 can be at least one of the factors responsible for the angiogenic processes required for atherosclerosis plaque development, we hypothesized that either of them could be upregulated in the vascular wall of apoE−/− mice.…”
Section: Introductionmentioning
confidence: 99%